If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -14 = 1 + y Reorder the terms: -14 + 4y = 1 + y Solving -14 + 4y = 1 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -14 + 4y + -1y = 1 + y + -1y Combine like terms: 4y + -1y = 3y -14 + 3y = 1 + y + -1y Combine like terms: y + -1y = 0 -14 + 3y = 1 + 0 -14 + 3y = 1 Add '14' to each side of the equation. -14 + 14 + 3y = 1 + 14 Combine like terms: -14 + 14 = 0 0 + 3y = 1 + 14 3y = 1 + 14 Combine like terms: 1 + 14 = 15 3y = 15 Divide each side by '3'. y = 5 Simplifying y = 5
| 5x+12(3x+49000)=4606000 | | 1/9c=-81 | | 60=-7x-5x | | |x+3|+10=8 | | |x+3|+100=8 | | 2=3-4n+3 | | 6x=7-(4y) | | 1(t)=15*3.2 | | 6(p-4)=4p-46 | | -1+y=-(5y-4) | | 8(-7.9)= | | 13.47+0.09(x+3)=13.97-0.11x | | -10n+5n(n+6)= | | xy+4=z | | 1/3x=-1/2 | | 62x19/31x1/4 | | 2/5x-7=-7 | | 19x-2+3x+6=180 | | 3n+24-n=50 | | 1+.8=2+.7 | | 14x-1/9-13x=17/9+14/9 | | 15+2x=7+x | | -4-11x-5=y | | e/-4+9=19 | | 4x+130+3x=40-3x | | 1+.80=2+.70 | | 4x-5=2(2x-4) | | 3/11+v=7/11 | | 1/10b=10 | | -5/3x+3/4-5/4+1/5 | | -5(2)+9= | | 7.2t=8*20 |